Systemic Glucocorticoid Therapy Reduces Pain and the Number of Endoneurial Tumor Necrosis Factor-Alpha (TNFα )-Positive Mast Cells in Rats With a Painful Peripheral Neuropathy - Reiko Hayashi; Wenhua Xiao; Masashi Kawamoto; Osafumi Yuge; Gary J. Bennett (Elsevier, 2008)
Clinical and experimental evidence suggests that glucocorticoids may be effective in the treatment of neuropathic pain, but their mechanism of action is unknown. We gave triamcinolone (3 mg/kg) to rats with an experimental post-traumatic painful peripheral neuropathy, chronic constriction injury (CCI), five days after nerve injury, when the abnormal pain syndrome is known to be present; and pain sensitivity was measured on postoperative days 7 -14, a period during which symptoms are known to be at approximately peak severity. Additional CCI rats were treated similarly; and then they were sacrificed five days after the injection for an immunocytochemical analysis of endoneurial tumor necrosis factor-alpha (TNFα ), macrophages, and mast cells in the sciatic nerve proximal to the site of injury. Vehicle-injected CCI rats demonstrated the expected neuropathic pain symptoms. Triamcinolone-treated CCI rats had a statistically significant reduction in the magnitude of heat-hyperalgesia and mechano-allodynia, but there was no effect on cold-allodynia or mechano-hyperalgesia. On the nerve-injured side of vehicle-injected rats, TNFα was present in Schwann cells and mast cells. On the nerve-injured side of triamcinolone-treated rats, there was a significant (71.5%) reduction in the number of TNFα-positive mast cells. Our results suggest that glucocorticoid therapy for neuropathic pain may work via the reduced expression of TNFα in endoneurial mast cells. Keywords:: glucocorticoid, hyperalgesia, mast cell, neuropathic pain, tumor necrosis factor-alpha (TNFα )